Transition from epoprostenol to selexipag in a patient with systemic sclerosis and pulmonary hypertension during the postoperative period of colon cancer surgery: A case report. Issue 2 (June 2022) - Wada, Takuma Tsuzuki; Yokota, Kazuhiro; Iida, Shinichiro; Kanno, Yuki; Shinozuka, Nozomi; Sato, Kojiro; Asanuma, Yu Funakubo; Yamamoto, Keiji; Mimura, Toshihide
Introduction: Most pulmonary vasodilators are administered orally; however, in patients with pulmonary hypertension undergoing gastrointestinal surgery, a switch to parenteral drugs is needed. Parenteral pulmonary vasodilators carry a risk of infection and reduced quality of life owing to long-term central venous catheterization; therefore, it is preferable to switch them to oral vasodilators after surgery. Here, we present the case of a patient with systemic sclerosis complicated by pulmonary hypertension and colon cancer, for which treatment was successfully switched from epoprostenol to selexipag postoperatively. Case Description: A 59-year-old woman, who was diagnosed with mixed group I and III pulmonary hypertension and systemic sclerosis, was on oral triple pulmonary vasodilators for pulmonary hypertension and Raynaud's phenomenon. She was diagnosed as having colon cancer 3 months before admission. Despite the severe pulmonary condition and treatment with oral triple pulmonary vasodilators, colon cancer resection surgery was performed with the management for pulmonary hypertension through multidisciplinary treatments in collaboration with cardiology specialists. Medications for patients with pulmonary hypertension undergoing gastrointestinal surgery need to be switched from oral vasodilators to epoprostenol perioperatively. On postoperative day 19, 0.4 mg/day of selexipag was administered with epoprostenol. Subsequently, the epoprostenol dosage was gradually decreased, and selexipag was increased. On postoperative day 30, the dose of selexipag was increased to 1.2 mg/day and epoprostenol was discontinued. The patient was discharged on postoperative day 40. Conclusion: In our case, transition from epoprostenol to selexipag contributed to a more useful management strategy for systemic sclerosis and pulmonary hypertension in the postoperative period.